Associations of Maternal Polyunsaturated Fatty Acids With Telomere Length in the Cord Blood and Placenta in Chinese Population - Liu, Xuanyi; Shi, Qiaoyu; Fan, Xiuqin; Chen, Hang; Chen, Na; Zhao, Yurong; Qi, Kemin (Frontiers in Nutrition, 2022)
Few studies have investigated the correlation between maternal polyunsaturated fatty acids (PUFAs) and telomeres in offspring, and the underlying influential mechanisms. In this study, we assessed the associations of maternal PUFAs with telomere length (TL) and DNA methylation of the telomerase reverse transcriptase (TERT) promoter in the cord blood and the placenta. A total of 274 pregnant women and their newborn babies were enrolled in this study. Maternal blood before delivery, the cord blood, and the placenta at birth were collected. Fatty acids in maternal erythrocytes and cord blood cells were measured by gas chromatography (GC). TL in the cord blood and the placenta was determined using real-time quantitative PCR (qPCR) by calculating the product ratio of telomeric DNA to the single-copy gene β-globin. The TERT promoter methylation was analyzed by DNA bisulfite sequencing. The associations of maternal fatty acids with TL were analyzed by univariate and multivariate regression. We found that low concentrations of docosapentaenoci acid (DPA, C22: 5n-3) and total n-3 PUFAs, adrenic acid (ADA, C22: 4n-6), and osbond acid (OA, C22: 5n-6) and high concentrations of linoleic acid (LA, C18: 2n-6) in maternal erythrocytes were associated with the shortened TL in cord blood cells (estimated difference in univariate analysis −0.36 to −0.46 for extreme quintile compared with middle quintile), and that low concentrations of cord blood docosahexaenoic acid (DHA, C22: 6n-3) were related to the shortened TL in cord blood cells. Differently, high concentrations of α-linolenic acid (LNA, C18: 3n-3), eicosatrienoic acid (EA, C20: 3n-3), DHA, and γ-linoleic acid (GLA, C18:3n-6) in maternal erythrocytes were associated with the shortened TL in the placenta (estimated difference in univariate analysis −0.36 to −0.45 for higher quintiles compared with the middle quintile). Further examination demonstrated that the concentrations of DHA and total n-3 PUFAs in maternal erythrocytes had positive associations with DNA methylation of the TERT promoter in the cord blood instead of the placenta. These data suggest that maternal PUFAs are closely correlated to infant TL and the TERT promoter methylation, which are differently affected by maternal n-3 PUFAs between the cord blood and the placenta. Therefore, keeping higher levels of maternal n-3 PUFAs during pregnancy may help to maintain TL in the offspring, which is beneficial to long-term health.